Geographical and environmental factors influence snow microbial communities in city and suburban areas of Northern China - Hengkang Xu; Yuchuan Shi; Siyi Wang; Chao Chen; Zhuo Pang; Guofang Zhang; Weiwei Zhang; Haiming Kan (Current Research in Microbial Sciences)
The response of snow microbial communities to environmental variations represents a critical topic in ecological research, particularly given that winter snowfall constitutes the main form of precipitation in northern China. In this study, snow samples were collected from city and suburb areas within the same region across seven provinces in northern China. The physical and chemical properties, metal ion content, and microbial community diversity and network stability were analyzed. Results indicated that the concentrations of Cu²⁺ and Na⁺ in city snow were significantly higher than those in suburb snow. While no significant differences were observed in the richness and diversity of bacterial and fungal communities between city and suburb areas, microbial network stability was higher in suburb samples. Latitude significantly influenced bacterial richness and Shannon diversity in city areas but not in suburb areas; however, fungal Shannon diversity in suburb snow showed a significant correlation with latitude. Mental analyses revealed that NO₃⁻ and chemical oxygen demand (COD) exerted distinct effects on bacterial communities in city and suburb areas, while TN, TC, and COD influenced fungal communities. Environmental factors were found to have significant impacts on microbial community structure, with geographical distance playing a key role in shaping snow microbial community composition. These findings highlight the influence of geographical location and environmental conditions on microbial diversity and community composition, offering valuable insights into the ecological impacts of urbanization and environmental changes on snow microbiomes.